Study on Nuclear Design of Long-life Lunar Surface Nuclear Reactor Power Supply Based on Annular Fuel - SHI Yunda1, ZHAO Shouzhi1, , SUN Zheng1, HU Binhe1, YUAN Xiaoming2, YANG Rui1 (Yuanzineng kexue jishu)
The space nuclear reactor power supply has the advantages of compact structure, high specific power, long service life, no dependence on light and strong environmental adaptability, making it the most ideal energy solution for lunar base. Taking the American FSP scheme as a reference, the net output power of 40 kW and the life span of 10 years were determined as the basic parameters of the nuclear power supply. For the power supply of space nuclear reactor for lunar base, thermal neutron reactor scheme is more competitive than fast neutron reactor scheme in reducing shielding mass and saving nuclear fuel. After comparing and analyzing several commonly used metal hydrides in space reactors, YH1.8 is chosen as moderator based on the principle of long service life. As an innovative fuel form, annular fuel has the characteristics of bilateral moderating and bilateral cooling, which can reduce the positive temperature effect of solid moderator and significantly improve the thermal safety margin of the reactor. It is the preferred fuel form for high-performance reactors in the future. TOPAZ-Ⅱ of the former Soviet Union is the most advanced type of space nuclear power supply that has been applied in engineering in the world at present, and its core physical scheme has a good reference significance. By referring to the core structure of TOPAZ-Ⅱ space reactor of the former Soviet Union and integrating the system structure of American FSP scheme, this core scheme was finally designed. By using annular fuel elements and optimizing lattice parameters, the problem of positive temperature effect of the whole reactor caused by solid moderator was solved. By introducing safety rod design, the problem of special criticality safety requirements was solved. By using YH1.8 as moderator, the hydrogen leakage problem of moderator was solved. The MCNP program was used as the calculation tool to complete the design and optimization of the core physics scheme, and all indicators meet the design requirements of space reactor. Compared with the FSP scheme, it is found that small thermal reactor is not necessarily at a disadvantage compared to small fast reactor in terms of core size parameters (including the reflector). Moreover, this scheme successfully reduced the 235U loading to 18.463 kg, which is only about a quarter of the FSP scheme, thus improving economy of the reactor.